Safety and immunogenicity of the M72/AS01E candidate tuberculosis vaccine in adults with tuberculosis: A phase II randomised study. (September 2016) - Gillard, Paul; Yang, Pan-Chyr; Danilovits, Manfred; Su, Wei-Juin; Cheng, Shih-Lung; Pehme, Lea; Bollaerts, Anne; Jongert, Erik; Moris, Philippe; Ofori-Anyinam, Opokua; Demoitié, Marie-Ange; Castro, Marcela
Summary: Previous studies have shown that the M72/AS01E candidate tuberculosis vaccine is immunogenic with a clinically acceptable safety profile in healthy and Mycobacterium tuberculosis -infected adults. This phase II, observer-blind, randomised study compared the safety, reactogenicity, and immunogenicity of M72/AS01E in 3 cohorts: tuberculosis-naïve adults (n = 80), adults previously treated for tuberculosis (n = 49), and adults who have completed the intensive phase of tuberculosis treatment (n = 13). In each cohort, 18–59-year-old adults were randomised (1:1) to receive two doses of M72/AS01E (n = 71) or placebo (n = 71) and followed-up until six months post-dose 2. Safety and reactogenicity were assessed as primary objective. Recruitment in the study ended prematurely because of a high incidence of large injection site redness/swelling reactions in M72/AS01E -vaccinated adults undergoing tuberculosis treatment. No additional clinically relevant adverse events were observed, except one possibly vaccine-related serious adverse event (hypersensitivity in a tuberculosis-treated-M72/AS01E participant). Robust and persistent M72-specific humoral and polyfunctional CD4 + T-cell-mediated immune responses were observed post-M72/AS01E vaccination in each cohort. In conclusion, the M72/AS01E vaccine was immunogenic in adults previously or currently treated for tuberculosis, but further analyses are needed to explain the high local reactogenicity in adults undergoing tuberculosis treatment. ClinicalTrials.gov:NCT01424501